Advances in Cyclometalated Iridium (III) Complexes: Emerging Strategies and Applications in Anticancer Therapy (London Journal of Research In Science: Natural and Formal, 2025)
Recently, the of organometallic iridium(III) complexes have attracted substantial interests in developing new metal-based antineoplastic drugs and this area of research has been intensively explored. Their various mechanisms of antitumor action are distinct from those of classical metal complexes, approved for clinical application. Different from the anticancer drugs of platinum-group metals, the described iridium(III) complexes principally act by damaging different intracellular organelles (mitochondria, lysosomes etc.), although the results are sporadic and no secure structure-activity relationship studies have been reported. On the other hand, organometallic Ir(III)-based complexes can overcome some of the limitations of Pt-based chemotherapy agents. Although they have only recently received significant consideration, Ir(III) complexes display an assortment of properties that make them exciting as prospective antineoplastic agents. Their chemical reactivity and binding preferences mainly depend on their coordination geometry ligands used. The structures of the metal-based antitumor agents, which consist of metal centers, biologically active auxiliary ligands, and their spatial arrangement, determine their biological profiles and cellular uptake. Amongst the various Ir(III) complexes studied for pharmacological activity, cyclometalated iridium complexes are mostly interesting because of their favorable photochemical and photophysical properties, including high stability under physiological conditions, luminescent properties, high emission quantum yields, long lifetime, large Stokes shifts, spectra ranging from VIS to NIR and affinity to participate in redox processes. That is why, these recognized series of highly luminescent organometallic complexes have been extensively studied for their different photophysical applications, especially as promising photosensitizers or phosphorescent agents in biosensing and biological imaging. A typical organometallic anticancer Ir(III) complex consists of an iridium(III) center bound to two cyclometalated C^N ligands and one N^N ancillary ligand. The modification of the cyclometalated ligands plays a dominant role in controlling the photophysical properties, whereas the alteration of the ancillary ligand allows functionalization with targets for imaging or therapy. Iridium complexes have been developed in order to find out their potential improved properties and better enhancement of the known therapies used.
Keywords: speciation; Biodiversity; Principle of Minimum Energy Expenditure; Open Systems; Dissipative Structures; Trophic Chain; ecological niches; evolutionary optimization; energy efficiency in biology; reduction of entropy.; Space and universe; existence and humanity; knowledge and information; subjective consciousness; objective reality.; LAB; Bacteriocins; Temperature stability; pH stability; Salt tolerance; abundance; diversity; Arthropods; natural; organic; inorganic; farming system; organometallic Ir(III) complexes; cyclometalated C^N and N^N ancillary ligand; antitumor agents.